Commitment and standards of Filipino married couples in performing household tasks - Avecilla, Nino Alvin Z.; Chua, Consuelo Trio. (2009.)
This study explored the commitment and standards of middle-income married couples in performing household tasks. It also determined the relationship between commitment in performing household tasks and employment hours; and the difference in commitment in terms of educational attainment, income level, and gender. Thirty couples were surveyed using the Household Task Performance Commitment Scale. Half of the respondents also answered an open-ended questionnaire about household standards. Data were analyzed using descriptive statistics, Pearson's correlation, T-test, ANOVA and content analysis. Results show that in general, wives have high level of commitment in performing household tasks, whereas husbands generally have an average commitment level. Furthermore, couple have a variety of standards in performing the following household tasks: laundry, ironing, dishwashing, menu planning, cooking, table setting, and general cleanliness of the house. On the other hand, husbands have more standards in terms of menu planning and general cleanliness of the house. There is a difference in the commitment level of husbands and wives in performing household tasks. Wives have a significantly higher commitment than husbands. However, the level of commitment in performing various household tasks does not differ in terms of income level and educational attainment. Recommendations for future research are provided at the end of the chapter.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Married people -- Philippines; Household tasks